2009
DOI: 10.3382/japr.2008-00140
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobials for foodborne pathogen reduction in organic and natural poultry production

Abstract: Antimicrobials currently used in the conventional poultry industry include physical, chemical, and biological hurdles. However, there is a need for natural and organic antimicrobials to make the food safe and to retain its natural taste and texture. Potential natural or organic antimicrobials include bacteriophages, bacteriocins, antibody therapy, vaccination, and the use of natural plant compounds such as essential oils. Genomic methods applied to salmonella responses to multiple interventions may offer oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…These stressors can originate as a wide range of physical and chemical challenges either in the environmental niches that Salmonella occupies or as manufactured barriers, such as those incorporated during food production and processing, such as antimicrobials, disinfectants, biocides, and preservatives. These intervention approaches have been reviewed extensively elsewhere (273,(287)(288)(289)(290)(291).…”
Section: Salmonella and Stress Responses In The Chicken Gitmentioning
confidence: 99%
“…These stressors can originate as a wide range of physical and chemical challenges either in the environmental niches that Salmonella occupies or as manufactured barriers, such as those incorporated during food production and processing, such as antimicrobials, disinfectants, biocides, and preservatives. These intervention approaches have been reviewed extensively elsewhere (273,(287)(288)(289)(290)(291).…”
Section: Salmonella and Stress Responses In The Chicken Gitmentioning
confidence: 99%
“…Different natural or organic alternative antimicrobials, such as bacteriocins, bacteriophages, and natural plant extracts such as essential oils and liquid smokes, have been studied for their antimicrobial activities against foodborne pathogens and food spoilage microorganisms (4,10,16,22,26). The commercial production of liquid smoke is typically done using a pyrolysis process involving thermal decomposition of wood (containing 10% moisture at 400 to 500°C) in retorts or rotary ovens under absence of oxygen, followed by a water spray to capture the resulting smoke and separation of the light and heavy fractions by gravity (1).…”
mentioning
confidence: 99%
“…However, studies have shown that when two antimicrobial treatments are applied to a food product, the application of the first treatment may cause the surviving bacteria to be resistant to the second treatment. Hence the first treatment may elicit protective mechanisms in the bacteria so that it may survive further stressors resulting in what has been referred to as crossprotection [252]. Therefore, it is crucial to devise proper strategies for applying the most effective combinations and sequence of antimicrobials to inhibit the contaminant bacteria in a way that they do not lead to crossprotection.…”
Section: Multiple Hurdle Strategiesmentioning
confidence: 99%
“…A hurdle technology is any treatment (physical, chemical, or biological) that is used to limit or eliminate the presence of pathogens and become "hurdles" to bacterial colonization and growth [252]. Such approaches are generally practiced in food processing.…”
Section: Multiple Hurdle Strategiesmentioning
confidence: 99%